Implementation of Module Based on Predict-Observe-Explain (POE) Integrated with Ethnoscience: Analysis of Relationship with Students' Concept Understanding - Damayanti, Selina; Syefrinando, Boby; Basuki, Fibrika Rahmat; Takiveikata, Sereima Baleisomi; Deporos, Saprolla Rollie C (Tekno - Pedagogi : Jurnal Teknologi Pendidikan, 2025)
This study aims to test the effectiveness of the Predict-Observe-Explain (POE)-based Physics module integrated with ethnoscience in improving students' conceptual understanding of static fluid material. This study used a quasi-experimental method with a one-group pretest-posttest design, involving 70 grade XI students at State Senior High School 8, Jambi City. Data were collected through pretests, posttests, and student response questionnaires. The t-test results showed a significant increase in student learning outcomes, where the average pre-test score of 65.4 increased to 85.7 after learning (p < 0.05). The Pearson correlation test showed a significant positive relationship between student responses to the module and conceptual understanding (r = 0.762, p < 0.05). These findings indicate that the POE-based module integrated with ethnoscience can improve students' conceptual understanding by linking scientific concepts with local wisdom. This study contributes to developing innovative teaching materials that are contextual and empirically evidence-based. Further research is recommended to expand the application of the module to other subjects and larger populations.